End-Stage Renal Disease-Related Accelerated Immune Senescence: Is Rejuvenation of the Immune System a Therapeutic Goal? - Ducloux, Didier; Legendre, Mathieu; Bamoulid, Jamal; Saas, Philippe; Courivaud, Cécile; Crepin, Thomas (Frontiers in Medicine, 2021)
End-stage renal disease (ESRD) patients exhibit clinical features of premature ageing, including frailty, cardiovascular disease, and muscle wasting. Accelerated ageing also concerns the immune system. It is now well documented that patients with ESRD have both immune senescence and chronic inflammation that are resumed in the so-called inflammaging syndrome. Immune senescence is particularly characterized by premature loss of thymic function that is associated with hyporesponsiveness to vaccines, susceptibility to infections, and death. ESRD-related chronic inflammation has multiple causes and participates to accelerated cardiovascular disease. Although, both characterization of immune senescence and its consequences are relatively well known, mechanisms are more uncertain. However, prevention of immune senescence/inflammation or/and rejuvenation of the immune system are major goal to ameliorate clinical outcomes of ESRD patients.